The Ethiopian higher education equity policy and its flaws - Leul Tadesse Sidelil (College of education, Bahir Dar University, 2023)
This paper seeks to examine and understand the Ethiopian higher education equity policy issues. It is document-based research using different policy and research documents and reports as primary and secondary sources of data. The basis for the analysis is laid down through the review of a range of literature in the area of equity in general and equity in higher education in particular. The analysis of this study reveals that although there are some strong political and legal bases, as well as policy provisions, the issue of equity in higher education in Ethiopia is addressed in a fragmented and insufficient way. The equity policies are found to be inadequate in terms of the equity groups identified and the equity measures prescribed. Moreover, some of the equity measures suggested appear to be ambiguous and short-sighted. The paper finally suggests the need to re-conceptualize the issues of equity in Ethiopian higher education policies in order to lay a comprehensive foundation to recognize the equity groups adequately, as well as to identify appropriate and sufficient equity measures.